Effect of Lactobacillus kefiri, in Conjunction with PENS T6 and a Hypocaloric Diet, on Weight Loss, Hypertension and Laboratory Glycemic and Lipid Profile - Ruiz-Tovar Polo, Jaime; Llavero, Carolina; Fernández Contreras, María Encarnación (My University, 2023)
The pathogenesis of obesity has been linked to alterations in gut microorganisms. The aim of this study was to investigate the effect of Lactobacillus kefiri, together with PENS T6 and a hypocaloric diet, on weight loss, hypertension and laboratory glycemic and lipid profile. A prospective non-randomized study was conducted involving adult patients with a body mass index (BMI) > 30 kg/m2. Patients were divided into two groups: those undergoing PENS-T6 and hypocaloric diet (PENS-Diet Group) and those undergoing the same PENS-T6 scheme and hypocaloric diet, but additionally receiving probiotics including Lactobacillus kefiri (PENS-Diet + L. kefiri Group). Weight loss was assessed at the end of the treatment, and analytical glycemic and lipid profile, and microbiological analysis of feces were performed before and after treatment. The addition of Lactobacillus kefiri to PENS T6 and a low-calorie diet, increases weight loss and further improves the glycemic and lipid profile. L. kefiri also causes a further improvement in obesity-associated dysbiosis, mainly by increasing the muconutritive (Akkermansia muciniphila) and regulatory (Bifidobacterium spp.) microbiome, and the Phylum Bacteroidetes (Prevotella spp.) and decreasing the Firmicutes/Bacteroidetes ratio. Keywords: Lactobacillus kefiri; PENS T6; obesity; metabolic syndrome; dysbiosis